Civic Consciousness in Professional Education of Specialists in International Relations - D. V. Pekushkina (Vestnik MGIMO-Universiteta)
The article analyses characteristic changes of civic and patriotic component in the modern world and notes characteristic features and problems in forming civic consciousness of university students. The author gives special attention to bringing up a citizen in the context of modernizing the system of education and studies the main aspects of building civic competence in students of international relations. The article further considers the correlation between the concepts of "civic consciousness" and "patriotism" at the present stage within the framework of professional training of international relations specialists who stand for state interests, and presents a historical survey of building civic consciousness in future diplomats at the Collegium of Foreign Affairs in the 18th-19th-century Russia. The author stresses the importance of building up civic responsibility and legal consciousness as a reflection of state interests. The author determines and gives solid grounding to the role of civic competence in the professional training of future international relations specialists in accordance with the Federal state education standards of higher education (3rd edition) showing the necessity of developing high professional responsibility based on axiological and spiritual values. The writer comes to the conclusion that it is necessary to study the philosophical, psychological and pedagogical aspects of the process of forming civic consciousness of international relations specialists.